In Hope's Shadow: Assisted Reproductive Technology and Neonatal Intensive Care. (2nd January 2016) - Kraemer, Susan; Steinberg, Zina
ABSTRACT: While assisted reproductive technologies (ART) have helped countless men and women become parents there are births that cast a long shadow. This article looks at ART from the little described vantage point of the Neonatal Intensive Care Unit (NICU), where newborn babies struggling to live meet their parents for the first time. Babies conceived through ART where more than one embryo is transferred are more likely to be multiples and multiple births are more frequently premature necessitating a NICU stay that can be long and arduous both for the infant and for the parents, often compounded with uncertain developmental outcomes. The technological salvation promised by ART is contrasted with the life and death realities of the NICU, including the despair, guilt and shame that NICU parents can feel. The complexities of how to counsel these hopeful prospective parents are discussed. Voice is given to the traumatic experience of these parents both in the NICU and then home.